The challenges faced by the enforcement bodies in Malaysia on human trafficking - Ab Hamid, Zuraini; Mohamad Amin, Noor Shuhadawati; Ab Aziz, Norjihan (International Organization Center of Academic Research (OCERINT)., 2017)
Excellence in the implementation of the legal framework on human trafficking by the enforcement bodies is one important benchmark that determines the success of Malaysia in the Trafficking in Persons (TIP) Report. The responsibility to enforce this framework is led by the Royal Malaysian Police (RMP) followed by the Immigration Department, the Customs Department, the Malaysian Maritime Enforcement Agency (MMEA), and the Department of Labour. Accordingly, Anti-Trafficking in Person unit is established in each body to acknowledge the power and trust granted to them. Normally located at the headquarters, these specialised units are dedicated to combat human trafficking. Furthermore, their actions are within the ambit of power granted by the legislated laws, particularly in Anti-Trafficking in Persons and Anti-Smuggling of Migrants Act 2007 (ATIPSOM 2007). All forms of exploitation including sex exploitation, labour force, and selling of babies which are common in Malaysia are highlighted by the Act. Unfortunately, since the introduction of TIP in 2001, these bodies have been continuously criticised by the reports, media, non-governmental organisations (NGOs), and public for their deficiency in identifying the vulnerable victims, detecting corruption among their officers, and failure in investigating the related cases. This article studies the power of these five enforcement bodies and the challenges that they face in combatting the heinous crime in order to understand the factors influencing their incompetency. A combination of content analysis and semistructured interview was adopted in the research. On the whole, the article contends that a lot of improvements need to be done to recuperate the image of these enforcement bodies and to strengthen their fight against human trafficking in Malaysia.